Keinginan dan Kebutuhan Sebagai Dasar Perencanaan Konsep Manajemen Pemasaran - Sufitrayati Sufitrayati; Safarina Safarina (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2025)
Changes in lifestyle, technological developments and market dynamics require companies to continue to innovate and adapt their marketing strategies. This can be achieved by understanding the evolving needs and desires of consumers. The aim of this research is to analyze and understand customer wants and needs as a basis for planning marketing management concepts. This study used qualitative research methods. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that consumer needs and desires are the main key in planning an effective marketing management concept. This is because needs and desires are the main motivation for consumers in making purchases. So by understanding consumer needs and desires, companies can develop marketing strategies that are right on target and effective in increasing sales and building customer loyalty.